Numerical Simulation Study on Evolution Process of Carrying-Soil Effect of Rectangular Pipe Jacking - Peng Ye; Bin Lan; Peng Zhang; Cong Zeng; Tianshuo Xu; Yong Xu; Rudong Wu (Buildings)
The carrying-soil effect is an important factor affecting the success or failure of rectangular pipe jacking construction. Because it is difficult to explore the dynamic evolution process of the carrying-soil effect in the field test, this paper relies on the pipe jacking project of a comprehensive pipe gallery in Suzhou City, and uses ABAQUS 2021 finite element software to simulate the jacking process of rectangular pipe jacking. Based on the theory of plastic mechanics of rock and soil and the related research and application status, the equivalent plastic strain index is introduced as the basis for judging the failure boundary of soil in the numerical simulation results, and the boundary between the carrying-soil area and the surrounding soil is determined, that is, the shear fracture surface. According to the principle of plastic potential energy, the development direction of the fracture surface is consistent with the direction of plastic flow, so as to predict the development direction of the boundary of the carrying-soil area. According to the change in the equivalent plastic strain cloud map with the jacking mileage, the evolution process of the carrying-soil effect is clarified, and the dynamic evolution law of the carrying-soil area is revealed, which is of great significance for predicting the disturbance of the surrounding soil during the construction of rectangular pipe jacking and accurately evaluating the environmental effect of the construction.